Outcomes of endovascular treatment for infrapopliteal peripheral artery disease based on the updated TASC II classification. (February 2021) - Müller, Arne M; Räpple, Veronika; Bradaric, Christian; Koppara, Tobias; Kehl, Victoria; Fusaro, Massimiliano; Cassese, Salvatore; Ott, Ilka; Kastrati, Adnan; Laugwitz, Karl-Ludwig; Ibrahim, Tareq
We retrospectively analyzed all endovascular procedures of infrapopliteal arterial lesions ( n = 383) performed in 270 patients at our institution between December 2008 and January 2018. The overall technical success rate was 97% and yielded 98% for stenoses ( n = 214) and 95% for occlusions ( n = 169). Trans-Atlantic Inter-Society Consensus (TASC II) classification had no impact on success rates (TASC A + B vs C + D; 96.5% vs 96.9%, p = 0.837). Freedom from clinically driven target lesion revascularization (TLR) after 6 and 12 months was 88.3% and 77.2%. TLR was comparable for TASC A to C lesions and no difference was observed comparing groups of moderately complex TASC A/B lesions and more complex TASC C/D lesions (TASC A + B vs C + D; 78.5% vs 74.2%, p = 0.457). Freedom from TLR was significantly lower in very complex TASC D lesions (TASC A + B + C vs D; 79.7% vs 42.5%, p < 0.001). Multivariate analysis identified TASC D lesions (hazard ratio D/A: 1.5; overall p = 0.002), Fontaine class III and IV (hazard ratio III or IV/IIa or IIb: 2.4; p = 0.041), and occlusive lesions (hazard ratio occlusion/stenosis: 2.4; p = 0.026) as predictors for TLR. In conclusion, endovascular therapy for infrapopliteal artery disease was safe and accompanied with a promising long-term outcome.